Donor substrate recognition in the raffinose-bound E342A mutant of fructosyltransferase Bacillus subtilis levansucrase - Meng, Guoyu; Fütterer, Klaus (BMC structural biology, 2008)
Background Fructans – β-D-fructofuranosyl polymers with a sucrose starter unit – constitute a carbohydrate reservoir synthesised by a considerable number of bacteria and plant species. Biosynthesis of levan (αGlc(1–2)βFru [(2–6)βFru] n ), an abundant form of bacterial fructan, is catalysed by levansucrase (sucrose:2,6-β-D-fructan-6-β-D-fructosyl transferase), utilizing sucrose as the sole substrate. Previously, we described the tertiary structure of Bacillus subtilis levansucrase in the ligand-free and sucrose-bound forms, establishing the mechanistic roles of three invariant carboxylate side chains, Asp86, Asp247 and Glu342, which are central to the double displacement reaction mechanism of fructosyl transfer. Still, the structural determinants of the fructosyl transfer reaction thus far have been only partially defined. Results Here, we report high-resolution structures of three levansucrase point mutants, D86A, D247A, and E342A, and that of raffinose-bound levansucrase-E342A. The D86A and D247A substitutions have little effect on the active site geometry. In marked contrast, the E342A mutant reveals conformational flexibility of functionally relevant side chains in the vicinity of the general acid Glu342, including Arg360, a residue required for levan polymerisation. The raffinose-complex reveals a conserved mode of donor substrate binding, involving minimal contacts with the raffinose galactosyl unit, which protrudes out of the active site, and specificity-determining contacts essentially restricted to the sucrosyl moiety. Conclusion The present structures, in conjunction with prior biochemical data, lead us to hypothesise that the conformational flexibility of Arg360 is linked to it forming a transient docking site for the fructosyl-acceptor substrate, through an interaction network involving nearby Glu340 and Asn242 at the rim of a central pocket forming the active site.